Heat Transfer Performance of Green Bioglycol-Based TiO2–SiO2 Nanofluids - S. N. M., Zainon; W. H., Azmi (American Society of Mechanical Engineers (ASME), 2021)
The dispersion of nanoparticles in conventional heat transfer fluids has been proven to improve the performance of the fluids. However, the study on the heat transfer performance of hybrid nanofluids in the mixture of water and green bioglycol (BG) is limited in the literature. This paper presents the heat transfer performance and friction factor of green BG-based TiO2–SiO2 nanofluids. The TiO2 and SiO2 nanoparticles were dispersed in the mixture of 60:40 water: bioglycol (W/BG) and prepared at various concentrations up to 2.5% and composition ratios of 20:80. The experimental study on forced convection heat transfer was done under turbulent flow at constant heat flux for operating temperature of 70 C. The heat transfer enhancement increased significantly with volume concentrations. The maximum heat transfer enhancements of the TiO2–SiO2 nanofluids at bulk temperature of 70 C were observed to be up to 67.81% for 2.5% volume concentration. A slight friction factor escalation of the nanofluids was observed with 12% maximum increment. New correlations were developed to estimate the Nusselt number, and friction factor with average deviations of less than 4.3%. As a conclusion, the employment of the ecofriendly coolant nanofluids in improving thermal performance is proven and applicable for turbulent forced convection heat transfer applications.